Modulation of the excitability of stellate neurons in the ventral cochlear nucleus of mice by TRPM2 channels - Bal, Ramazan; Ozturk, Gurkan; Etem, Ebru Onalan; Eraslan, Ersen; Ozaydin, Seda (Elsevier, 2020)
Oxidative stress-induced Ca2+ permeable transient receptor potential melastatin 2 (TRPM2) channels are expressed at high levels in the brain, appear to link neuronal excitability to cellular metabolism, and are involved in the pathogenesis of neurodegenerative disorders. We aimed to study the electrophysiological properties of TRPM2 channels in stellate cells of the mouse ventral cochlear nucleus (VCN) using molecular, immunohistochemical and electrophysiological approaches. In the present study, the real time PCR analysis revealed the presence of the TRPM2 mRNA in the mouse VCN tissue. Cell bodies of stellate cells were moderately labeled with TRPM2 antibodies using immunohistochemical staining. Stellate cells were sensitive to intracellular ADP-ribose (ADPR), a TRPM2 agonist. Upon the application of ADPR, the resting membrane potential of the stellate cells was significantly depolarized, shifting from -61.2 +/- 0.9 mV to-57.0 +/- 0.8 mV (P < 0.001; n = 21), and the firing rate significantly increased (P < 0.001, n = 6). When the pipette solution contained ADPR (300 mu M) and the TRPM2 antagonists flufenamic acid (FFA) (100 mu M), N-(p-amylcinnamoyl) anthranilic acid (ACA) (50 mu M) and 8-bromo-cADP-Ribose (8Br-cADPR) (50 mu M), the membrane potential shifted in a hyperpolarizing direction. ADPR did not significantly change the resting membrane potential and action potential firing rate of stellate cells from TRPM2-/- mice. In conclusion, the results obtained using these molecular, immunohistochemical and electrophysiological approaches reveal the expression of functional TRPM2 channels in stellate neurons of the mouse VCN. TRPM2 might exert a significant modulatory effect on setting the level of resting excitability.
Keywords: Stellate cells; Cochlear nucleus; TRPM2 channels; TRP channel Family